Femtosecond Laser-Assisted In Situ Keratomileusis Treatment of Residual Refractive Error following Femtosecond Laser-Enabled Keratoplasty. (29th August 2019) - Shen, Elizabeth; Tsai, Lester; Muniz Castro, Hannah; Wade, Matthew; Farid, Marjan
Abstract : Purpose . To evaluate the safety and effectiveness of femtosecond laser-assisted in situ keratomileusis (LASIK) in the treatment of residual myopia and astigmatism following femtosecond laser-enabled keratoplasty (FLEK). Design . Retrospective case review. Methods . Chart review of all patients with prior FLEK who subsequently underwent femto-LASIK surgery after full suture removal was performed at the Gavin Herbert Eye Institute at the University of California, Irvine. A total of 14 eyes in 13 patients met this criterion, and their comprehensive examinations performed at standard intervals were reviewed. Main outcome measures include uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA) expressed as the logarithm of the minimum angle of resolution (logMAR), manifest refractive astigmatism, and spherical equivalent. Results . From the preoperative visit to the 3 month visit, all 14 eyes significantly improved in UDVA (logMAR, 0.93 ± 0.23 to 0.44 ± 0.32, P = 0.002 ) with no loss of CDVA (logMAR, 0.26 ± 0.19 to 0.18 ± 0.23, P = 0.50 ). All 14 eyes showed significant improvement in manifest refractive astigmatism (4.71 ± 1.77 to 2.18 ± 1.45 diopters (D), P = 0.003 ) and spherical equivalent (−2.57 ± 2.45 to −0.48 ± 0.83 D, P = 0.0007 ). There were no flap or graft complications as a result of femto-LASIK. Conclusions . Our findings suggest that femto-LASIK on eyes with prior FLEK is safe and effective in improving visual acuity and reducing residual astigmatism.